A Mendelian randomization analysis of inflammatory skin disease risk due to mineral deficiencies - Wu, Ronghui; Tian, Hao; Zhao, Tianqi; Tian, Yangyang; Jin, Xianhua; Zhu, Mingji (Frontiers in Nutrition, 2024)
Background: Mineral deficiencies, such as iron (Fe), zinc (Zn), and selenium (Se), play crucial roles in inflammation and immune responses and are linked to chronic inflammatory skin diseases. This study used genome-wide association study (GWAS) data and Mendelian randomization (MR) to investigate the genetic causality among serum levels of five minerals (Fe, Cu, Zn, Se, Ca), three iron metabolism indicators (TSAT, TIBC, ferritin), and three chronic inflammatory skin diseases (psoriasis [PS], atopic dermatitis [AD], acne vulgaris [AV]).Methods: Two-sample MR analyses using the "TwoSample MR" package in R were conducted with aggregate outcome data from the FinnGen database. The inverse-variance-weighted (IVW) method was applied to assess causal relationships between mineral levels and disease outcomes. Robustness was examined via heterogeneity and pleiotropy tests.Results: IVW analysis showed significant association between blood transferrin saturation (TSAT) and PS (p = 0.004, OR = 1.18). Serum Zn and Se levels showed inverse correlation with AD (p = 0.039, OR = 0.92). However, due to limited SNPs, robustness was reduced.Conclusion: TSAT is genetically linked to PS, highlighting iron homeostasis in disease development. Zn and Se intake may reduce AD risk.